Analisa Kerusakan Perkerasan Lentur (Flexible Pavement) Pada Ruas Jalan Pacing-Pacet kabupaten Mojokerto Dengan Metode 1 Pavement Condition Index (PCI) - Ery Dharmawan; Bambang Suprapto; Azizah Rachmawati (Jurnal Rekayasa Sipil, 2020)
Analysis the damage flexible pavement by method pavement condition index (PCI) on the Pacing-Pacet road section, road pavement damage assessment system thatrefers to the type, dimensions, and level of damage that occurred, and can be oneof the references to determine the type of maintenance of road pavement damage.The Pacing-Pacet road section has become one of the main accesses, resulting inmany vehicles crossing the Pacing-Pacet road section, so that the burden receivedby the road becomes greater which will result in damage to the pavement. Thisstudy aims to determine the pavement conditions on the Pacing-Pacet road usingthe pavement condition index (PCI) method with a section length of 21 km dividedinto 42 segments where each segment has a size of 500 x 9 m. Analysis of eachsegment is done visually in the field by measuring the dimensions of the damage,identification of the type of damage, and the level of damage to determine the valueof the pavement condition index (PCI). The results of visual surveys in the fieldfound types of damage such as fillings, holes, sinks, wear, obesity, crocodile skincracks, longitudinal and transverse cracks, groove cracks, and without damage.The PCI value on the Pacing-Pacet road segment is 26, which means that thepavement conditions on the Pacing-Pacet road segment are bad, so the type ofmaintenance used is periodic maintenance so that the damage that occurs on thePacing-Pacet road section is not getting worse.Keywords: road damage analysis, type of road damage, PCI.